Better antioxidant capacity in elite female soccer players compared to sub-elite players - Gravina, L.; Zubero, J.; Ruiz, F.; Irazusta, J.; Lekue, J.; Gil, S. M. (Archivos de medicina del deporte, 2008)
Oxidative stress has been the subject of study of many research projects for the last years. Most of the studies have reported the presence of oxidative stress as a consequence of intense physical activity in some sports, such as soccer. However, no studies have shown whether a higher level of playing or training intensity may improve the antioxidant defence mechanism against oxidative stress. Thus, the purpose of the study was to determine the antioxidant capacity in elite and sub-elite women soccer players during a soccer match. Methods: 28 female soccer players from the Athletic Club of Bilbao participated in this study: team A (playing in the Superliga, mean age 25 ± 5.1, n=14) and team B (playing Northern League, mean age 18 ± 1.7, n=14). Blood samples were obtained 24h before, immediately after and 18h after a competition match. Serum levels of Total Antioxidant Status (TAS), Superoxide Dismutase (SOD), Glutathione Reductase (GR), Glutathione Peroxidase (GPx), Bilirubin, Albumin (Alb), Ferritine, and Uric Acid (UA) were measured. Student-t test for independent samples was used for the statistical analysis. Results: At rest TAS and GPx activity were significantly higher in team A compared to team B (p<0.001). This difference was maintained immediately after and 18h after the soccer match. Team A also had SOD activity higher inmediately after a match (p<0.05) and 18h post-match (p<0.01). Team B, however, presented a higher GR activity 18h post-match (p<0.05). No significant differences were observed in the rest of the parameters. Conclusions: The elite team had better antioxidant capacity than the sub-elite team, particularly, after playing a match. It is possible that training at higher intensity and level produces a better and/or faster defensive response to oxidative stress. Deskriptoren